Fundamental Principles of the Ideal Islamic Community (Khair Ummah) in Preserving Religious Solidarity in the Islamic World - Barazili, Sigit; Syukur, Abdul (EDUCATIO : Journal of Education, 2023)
This study delves into the concept of the ideal Islamic society, often known as "Khair Ummah," aimed at preserving religious solidarity among the global Muslim community. It employs a qualitative research approach, analyzing Islamic teachings and literature, including Surah Al-Hashr (59:7), to emphasize the core principles of social justice, equitable wealth distribution, education, and Islamic brotherhood. The findings underscore that an ideal Islamic society prioritizes justice, equality, and the well-being of its members and stresses harmonious relationships among Muslims and tolerance for different faiths, fostering a just, prosperous, and mutually supportive society. To actualize this vision, policymakers and community leaders should implement measures supporting social justice, fair wealth distribution, and education while promoting interfaith dialogue and understanding to enhance tolerance and inclusivity.